Somatosensory Evoked Field in Response to Visuotactile Stimulation in 3- to 4-Year-Old Children - Remijn, Gerard B.; Kikuchi, Mitsuru; Shitamichi, Kiyomi; Ueno, Sanae; Yoshimura, Yuko; Nagao, Kikuko; Tsubokawa, Tsunehisa; Kojima, Haruyuki; Higashida, Haruhiro; Minabe, Yoshio (Frontiers in Human Neuroscience, 2014)
A child-customsized magnetoencephalography (MEG) system was used to investigate somatosensory evoked field (SEF) in 3- to 4-year-old children. Three stimulus conditions were used in which the children received tactile-only stimulation to their left index finger, or visuotactile stimulation. In the two visuotactile conditions the children received tactile stimulation to their finger while they watched a video of tactile stimulation applied either to someone else’s finger (the finger-touch condition), or to someone else’s toe (the toe-touch condition). The latencies and source strengths of equivalent current dipoles (ECD) over contralateral (right) somatosensory cortex were analyzed. In the preschoolers who provided valid ECDs, the stimulus conditions induced an early-latency ECD occurring in between 60-68 ms mainly with an anterior direction. We further identified a middle-latency ECD in between 97-104 ms, which predominantly had a posterior direction. Finally, initial evidence was found for a late-latency ECD at about 139-151 ms again more often with an anterior direction. Differences were found in the source strengths of the middle-latency ECDs among the stimulus conditions. For the paired comparisons that could be formed, ECD source strength was more pronounced in the finger-touch condition than in the tactile-only and the toe-touch condition. Although more research is necessary to expand the data set, this suggests that visual information modulated preschool SEF. The finding that ECD source strength was higher when seen and felt touch occurred to the same body part, as compared to a different body part, might further indicate that connectivity between visual and tactile information is indexed in preschool somatosensory cortical activity, already in a somatotopic way.